THE CORRELATION BETWEEN PARENTS EDUCATIONAL BACKGROUND AND STUDENTS’ MOTIVATIONS IN LEARNING SPEAKING - Setia Widya; Eva Faliyanti; Aulia Hanifah Qomar (Journal of English Education and Entrepreneurship (JEEP), 2024)
Speaking is a form of communication that involves various factors that can influence a person's motivation to learn it. These factors include family dynamics such as parental attention, family relationships, home environment, economic status, and cultural background. Additionally, the educational background of the parents can also shape a student's motivation to learn speaking. This research aims to find out the correlation between parents’ educational background and students motivations in Learning Speaking of the students of English education at Muhammadiyah University of Metro. This research utilized a correlation research design by 40 students to become sample of this research. This research used a questionnaire to determine student motivation and parents educational background. The results of this research indicate that there is no correlation between parents' educational background and students' motivations in Learning Speaking with the Correlation Coefficient value is smaller than 0 (-0.93 <0), while the sig value is greater than 0.05 (0.451>0.05) which means that there is no significant positive correlation between the educational background of parents and students' motivations. In conclusion, this research underlines the complexity of factors influencing students' motivation and highlights the need for further approaches to improve learning outcomes in speaking skills. Future researchers should examine additional variables that may influence students’ motivation to learn speaking skills, such as socioeconomic status, teacher-student relationships, and extracurricular activities.